AB1012 HENOCH-SCHöNLEIN PURPURA AND UVEITIS, AN UNUSUAL ASSOCIATION. (June 2019) - Maccora, Ilaria; Tirelli, Francesca; Simonini, Gabriele; Giani, Teresa; Cimaz, Rolando
Abstract : Background: Henoch-Schönlein purpura (HSP) is the most common childhood vasculitis characterized by cutaneous palpable purpura predominantly located in the lower limbs, arthralgia/arthritis, renal and bowel involvement. To our knowledge only 4 cases of HSP with ocular involvement have been reported so far. Objectives: We describe a 6-year-old female patient who presented HSP and panuveitis. Methods: Describe a case report. Results: A 6-year-old female, previously in good health, received the diagnosis of HSP for cutaneous palpable purpura on her lower limbs, bilateral ankle arthritis and haematuria. Two weeks later the girl was admitted to our Emergency Department due to monolateral ocular pain with red eye. At ophthalmological assessment there was evidence of anterior uveitis with and edema of the optic disc. Blood tests showed increased values of CRP (1.92 mg/dl) and ESR (69 mm/h) with normal values of complement levels and complete blood count. Urinalysis displayed mild hematuria and proteinuria. Immunoglobulin levels were slightly increased: IgG (1850 mg/dl, n.v. 540-1330 mg/dl), IgA 244 mg/dl (n.v. 50-240 mg/dl) and IgM 72 mg/dl (n. v. 50-180 mg/dl) An extensive infectious work-up for viral, bacterial and parasitic infections was negative. ANA, ANCA, ASCA, LAC, HLA B27 and B51 were all negative. Chest X ray, abdominal ultrasound and echocardiography were negative. A brain MRI with contrast revealed an iris inflammation and excluded CNS involvement. Systemic therapy was started with i.v. methylprednisolone (30mg/kg/d for three consecutive days) and continued with oral prednisone (2 mg/kg/day), with a progressive improvement of the ocular, skin, nephrological and articular involvement. Prednisone was then gradually tapered over 2 months without disease recurrence. Conclusion: In our literature search we were able to find an association between HSP and uveitis only in two adults and in an 11-year-old child. All these patients showed cutaneous and articular involvement and 3/4 nephrological involvement. Uveitis was observed in the first week of vasculitis onset. Although rare, the presence of ocular involvement can occur during HSP. References: [1] Ozen S, et al. EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part II: Final classification criteria. Ann Rheum Dis. 2010 May;69(5):798-806. [2] Kaur S. et al. Henoch–Schonlein purpura with uveitis: an unusual case and review of literature. Rheumatol Int (2012) 32:4057–4059 Disclosure of Interests: Ilaria Maccora: None declared, Francesca Tirelli: None declared, Gabriele Simonini Grant/research support from: Abbvie, Speakers bureau: Abbvie, Teresa Giani: None declared, Rolando Cimaz: None declared